Marketing Strategy and Capability as the Mediators in Relationship of Market Orientation and Export Performance: A Case Study of Rattan Processing SMEs - Indra Muis (Bina Nusantara University, 2020)
The research examined the performance of export marketing performance through the implementation of market orientation intervened by export marketing strategy and export marketing capability. Primary data were collected through questionnaires from 108 samples out of 148 rattan processing Small and Medium Enterprises (SMEs) in nine provinces in Indonesia. The respondents were marketing managers or owners of SMEs with at least two years of experience. Structural Equation Modeling (SEM), which was processed by using Lisrel 8.7, was employed. The results indicate that market orientation, export marketing strategy, and export marketing capability are well implemented in the business operation of SMEs. However, the export marketing performance needs to be improved. Concerning the variables studied, market orientation has a significant effect on export marketing strategy, export marketing capability, and export marketing performance. Then, export marketing strategy affects export marketing performance significantly. Moreover, export marketing capability also has a significant effect on export marketing performance. Finally, export marketing strategy and capability intervene in the relationship between market orientation and export performance.